Applied islamic law of trade and finance - Mohd Ma'sum Billah (Sweet & Maxwell Asia, 2007)
Trade and finance arranged according to Islamic principles have gained increasing importance. Commercial transactions conducted under Shari’ah principles form a significant portion of international commercial activity today and the Shari’ah trade and finance system has now developed into an important system operating parallel to the conventional system.